PENGEMBANGAN E-MODUL BERBASIS HEYZINE FLIPBOOK MATERI MITIGASI BENCANA UNTUK SISWA KELAS XI IPS SMAN 1 SINGOSARI - heppy mafudhotul auwaliyah; Alfi Sahrina; Hadi Soekamto; Heni Masruroh (JURNAL GEOGRAFI, 2023)
This study was motivated by the weak teaching materials used and the low use of technology-based teaching materials. One way to overcome this problem is to make teaching materials in the form of Heyzine flipbook[1]based E-modules. The purpose of this study was to create teaching materials for geography E-modules on disaster mitigation material based on Heyzine flipbook. The method used is the ADDIE model (analysis, design, development, implementation and evaluation). Data collection is done through observation, expert validation and user response. The questionnaires used were in the form of expert validation sheets and user response sheets (students and geography subject teachers). The data collected were data on the quality of teaching materials and recommendations from design, material, and language expert validators, as well as data on user responses to teaching materials by students and teachers. The data were processed using quantitative descriptive methods. The results of the E-module validation received a percentage score of 95.60% from design experts, 92.19% from material experts and 86.80% from language experts. The results of summative evaluation questions during implementation from 27 students, 85% of students with very high scores, 4% of students with high scores, 4% of students with medium scores, 4% of students with low scores and 3% of students with very low scores. The results of student responses obtained a percentage of 88.03% Indicators with the highest percentage are points 1 and 11 of the physical appearance of the E-module that attracts students to read and E-modules can be used at any time, which means that this Heyzine flipbook based E-module can be easily accessed by students while Geography teachers give a percentage of 100%